Visual Character of Colonial Building Facade in Suroyo Street Corridor, Probolinggo City Indonesia - Ronarizkia, Adita; Giriwati, Novi Sunu Sri (University of Merdeka Malang, 2020)
Suroyo street corridor located in the City of Probolinggo is one of the central areas of the Dutch government that has several conservation buildings as a historical identity of the city. Colonial buildings in this location have various facades that are able to describe the visual characteristics of the historic area. However, there were developments that affect the modernity of the region by changing colonial buildings into other functions and changing some facade elements which will certainly eliminate some of the visual characteristics of colonial building facades on each building. The purpose of this study is to classify the facade forming elements and get the dominant form in each element that forms the facade of the remaining colonial buildings, so it wouldn't lose the overall visual character of the colonial building facade and to be able to respond to the development of a more directed and controlled. The method that were used is descriptive qualitative methods by selecting samples using purposive sampling, then proceed with data collection through field observations and interviews to obtain relevant information and analysis by classifying building masses, walls, roof elements, doors, windows and facade symmetry. The results showed the visual character of the colonial building with the style of De Stilj with the classification of the dominance of a single mass, roof shield, paint plaster brick walls, double-paneled doors, double-windowed grating, and the symmetrical shape of the building facade.Â DOI: https://doi.org/10.26905/lw.v12i1.3833